Owner‐Managers and the Failure of Newly Adopted Works Councils. (7th September 2015) - Jirjahn, Uwe; Mohrenweiser, Jens
Abstract: Using representative data from the IAB Establishment Panel, we show that the managerial environment has a strong influence on the introduction and survival of works councils. Employees in owner‐managed establishments are less likely to introduce a works council. Moreover, in case of an introduction, the new works council is less likely to survive if the establishment is owner‐managed. The pattern of results even holds in situations that involve positive economic effects of works councils. This suggests that owner‐managers oppose works councils not primarily for economic reasons. Our findings are rather consistent with the hypothesis that owner‐managers oppose co‐determination because it reduces the utility they gain from being the ultimate bosses within the establishment.